Pengaruh Performance Quality, Reputasi Merek Dan Kepuasan Pelanggan Terhadap Loyalitas Merek - Fakhrudin, Arif (Universitas Muhammadiyah Yogyakarta, 2016)
Generally, the aims of a company are to survive and to earn provits. The profits ave earned when the customers use the products or the service offered by the company. This study aims at analyzing the factors which influence the customers loyalty using the Jogja Trans 8 transportation service. The variables involve performance quality (X1), brand reputation (X2), customers satisfaction (X3). The varibles were tested using spss 11.5. The result show that performance quality was not significanttly correlated to brand loyalty (0,210), and brandreputation was not significantly corelated to brand loyalty (0,168), and then customers satisfaction significantly correlated to brand loyalty (0,01)